2020
DOI: 10.3390/jcm9061636
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification in Hypertrophic Cardiomyopathy. Insights from Genetic Analysis and Cardiopulmonary Exercise Testing

Abstract: The role of genetic testing over the clinical and functional variables, including data from the cardiopulmonary exercise test (CPET), in the hypertrophic cardiomyopathy (HCM) risk stratification remains unclear. A retrospective genotype–phenotype correlation was performed to analyze possible differences between patients with and without likely pathogenic/pathogenic (LP/P) variants. A total of 371 HCM patients were screened at least for the main sarcomeric genes MYBPC3 (myosin binding protein C), MYH7 (β-myosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 45 publications
1
25
0
1
Order By: Relevance
“…Indeed, besides the occurrence of the well-known disease-related complications (i.e., atrial fibrillation or end-stage phase), myocardial fiber disarray, interstitial fibrosis, microvascular ischemia, chronotropic incompetence, as well as LVOT obstruction, are all factors able to impact negatively on diastolic and systolic left ventricular function at rest and, particularly, during exercise [ 17 ]. Although each of the abovementioned clinical features might concur theoretically to an exercise impairment also in pediatric HCM patients, it might be conceivable that, particularly in this setting, the genetic burden might play the greatest role through a direct impact on the cardiomyocytes’ efficiency [ 15 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, besides the occurrence of the well-known disease-related complications (i.e., atrial fibrillation or end-stage phase), myocardial fiber disarray, interstitial fibrosis, microvascular ischemia, chronotropic incompetence, as well as LVOT obstruction, are all factors able to impact negatively on diastolic and systolic left ventricular function at rest and, particularly, during exercise [ 17 ]. Although each of the abovementioned clinical features might concur theoretically to an exercise impairment also in pediatric HCM patients, it might be conceivable that, particularly in this setting, the genetic burden might play the greatest role through a direct impact on the cardiomyocytes’ efficiency [ 15 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Last, most recently, in nearly 400 pediatric HCM patients (median age 14 years and median follow-up 5.9 years), Alashi et al found the presence of symptoms as an important feature associated with the primary composite outcome of SCD-related events, septal reduction procedure due to HF worsening and cardiac transplantation [ 37 ]. Accordingly, it is highly reasonable that a more reliable functional classification in pediatric HCM patients might further improve also their risk stratification as it has been proven yet in adult HCM patients [ 10 , 11 , 12 , 13 , 14 , 15 ]. Our data support the abovementioned hypothesis given that the most important CPET-derived variable, namely, the pVO 2 , was greatly impaired in those HCM patients who experienced a cardiac event during the follow-up and univariately associated to the tested end-point.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations